A cost-effectiveness analysis of E/C/F/TAF vs three boosted regimens in the Italian context - Pradelli, Lorenzo; Di Perri, Giovanni; Rizzardini, Giuliano; Martelli, Elisa; Giardina, Stefano; Povero, Massimiliano (Farmeconomia. Health economics and therapeutic pathways, 2017)
BACKGROUND: Highly Active Antiretroviral Therapy (HAART) has transformed HIV into a lifelong condition. Following the chronicity of the disease, and significant increase in lifespan – the prevalence of comorbidities increased in HIV+ subjects that are exposed both to a higher risk of developing cardiovascular disease, renal disease, osteopenia/osteoporosis and diabetes, and to the risk of developing them early. Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Alafenamide Fumarate (E/C/F/TAF), a complete, Single-Tablet antiretroviral Regimen (STR) that combines the effectiveness and tolerability of integrase inhibitors with an innovative backbone was recently introduced in Italy. Compared to Tenofovir Disoproxil Fumarate (TDF), TAF reaches the sites of action more efficiently, reducing tenofovir plasma concentration to more than 90% and the risk of off-target effects. OBJECTIVE: A patient-level micro-simulation model was adapted to the Italian context to evaluate E/C/F/TAF cost-effectiveness vs three boosted regimens for HIV+ patients treatment. METHODS: A Markov micro-simulation model was adapted to the Italian context for the evaluation of the cost-effectiveness in patients with HIV. The total cost per patient accounts for drug therapies and the management of adverse events and comorbidities. The quality-adjusted life expectancy (in QALYs) is calculated by weighing the years of life lived by the utility weights. A 70-year time horizon was adopted to simulate a lifetime analysis; shorter time horizons were considered in the sensitivity analyses. 3.5% discount rate was applied both for costs and future benefits. The rate of virologic suppression at 48 weeks with E/C/F/TAF is 92.3%; for the other treatments such proportion is calculated by applying to the reference rate the relative risks, as calculated in a recent network meta-analysis (NMA). Alternative treatments considered in this analysis are three boosted regimens commonly used in Italy: tenofovir disoproxil fumarate/emtricitabine/elvitegravir/cobicistat in STR; tenofovir disoproxil fumarate/emtricitabine + darunavir/ritonavir; tenofovir disoproxil fumarate/emtricitabine + atazanavir/ritonavir. RESULTS: E/C/F/TAF improves survival and quality of life (20.17 LY and 14.89 QALY), with the lowest total cost (€ 280,528), thus resulting dominant over three comparators considered as starting therapy. The sensitivity analysis confirms the results of the base case: at a willingness-to-pay threshold of € 30,000 per QALY, the E/C/F/TAF strategy is the most cost-effective, with a 90% probability and it is the most cost-effective even with a threshold of € 10,000 per QALY, with a 50% probability. CONCLUSION: E/C/F/TAF can be a sustainable alternative to currently available treatments, combining the advantage of the STR to lower risks of kidney and bone damage than observed in regimens based on TDF.